Synthesis, characterization, photophysical and thermal properties of cyclotriphosphazene compounds containing N-heterocyclic fluorophores - Palabiyik, Duygu; Besli, Serap (Elsevier Science Sa, 2025)
The new inorganic-organic hybrid tripod structures containing cyclotriphosphazene, carbazole, indole, and quinoline groups were successfully designed, synthesized, and characterized. The particularities of synthesized compounds were confirmed using spectroscopic techniques (1H, 13C, 31P NMR, and mass spectroscopy) and elemental analysis. The absorption and emission properties of the new hybrid molecules (3a, 5b, 7, and 8) were investigated in different solvents and compared with each other. The dynamic/static quenching in the presence of 6-oxyquinoline was discussed for 3a and 5b, supported by the photophysical parameters. Thermal analyses of the compounds 3a and 5b were performed by thermal gravimetric analysis (TGA), thus determining their char yields and temperatures of decomposition processes.
Keywords: Cyclotriphosphazene; Synthesis; Characterization; Spectroscopy